Night Market as Lived Space: The Case of Davao City, Philippines - Pavo, Raymundo R. (Animo Repository, 2019)
This paper explores and examines the Roxas Night Market in Davao City as lived space. Following Lefebvre’s (2014) idea of space as lived this paper looks into their migration story that led to their inclusion in the night market, which helped condition the symbolic meanings that they attach to the site. Using the case study as the privileged research design of this investigation, this approach upholds two saturation points: first, the numbers of vendors have been limited to nine after their stories have reached a repetitive story line, and second, the theory of Lefebvre (2014) on space as lived has been satisfied. Conforming to the assumptions of a descriptive-qualitative approach, the stories of the vendors are convened and analyzed from which unfolding themes are identified. To critically appraise the descriptions, de Certeau’s (1984, 1992) concept of perpetual departures and strategies is used. With the critical vantage point, the night market is construed not simply as a gathering of histories and anticipations of the future of migrants who became street vendors in the city but as a location where creative and practical capacities or agencies are demonstrated. Considering the regulative role of their stories, the Roxas Night Market as lived space further means that it forms part of the vendors’ long journey and quest for enabling and fulfilling spaces of work, and overall well-being.